1981
DOI: 10.1002/nur.4770040303
|View full text |Cite
|
Sign up to set email alerts
|

Empathic perceptions of nursing students: Self‐reported and actual ability

Abstract: Clearly, one of the goals of nursing education is to enhance the empathic functioning of nursing students. In this study we examined one major component of empathic functioning--accuracy of empathic perceptions--in both undergraduate (n = 66) and graduate nursing students (n = 50) We predicted that actual ability (Kagan's Affective Sensitivity Scale) and self-perceived ability would vary as a positive function of educational level. The results supported the first prediction, even when the effects of the subjec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
5
0
1

Year Published

1990
1990
2020
2020

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 23 publications
(7 citation statements)
references
References 28 publications
1
5
0
1
Order By: Relevance
“…Similar to previous study with American samples (Hojat et al 2002b), the empathy mean score for women was significantly higher than that for men, however, in a study with Italian physicians no gender difference on empathy was found (Di Lillo et al 2009). The consistent findings in several studies, including our study that women score higher than men on empathy can be explained by female's higher sensitivity in interpersonal relationship, and their better understanding of patient's emotional signals (Hojat 2007) which can lead to a better empathic engagement in patient care (Kunst-Wilson et al 1981;Newton et al 2008).…”
Section: Discussionsupporting
confidence: 87%
“…Similar to previous study with American samples (Hojat et al 2002b), the empathy mean score for women was significantly higher than that for men, however, in a study with Italian physicians no gender difference on empathy was found (Di Lillo et al 2009). The consistent findings in several studies, including our study that women score higher than men on empathy can be explained by female's higher sensitivity in interpersonal relationship, and their better understanding of patient's emotional signals (Hojat 2007) which can lead to a better empathic engagement in patient care (Kunst-Wilson et al 1981;Newton et al 2008).…”
Section: Discussionsupporting
confidence: 87%
“…Nursing authors have presented this communication process as a two-phase (Kunst-Wilson et al 1981), three phase (Kalisch 1973, Zderad 1970 or four-phase (Ehmann 1971) model, all of which are based on a conceptualization of empathy as developed in counselling psychology. The uncritical adoption of empathy by nursing remains a poor fit with the clinical situation, and the use of therapeutic empathy has not influenced nursing practice or patient outcomes as dramatically as expected (Kalisch 1973, La Monica et al 1987, Reynolds & Presly 1987.…”
Section: The Empathetic Model Of Communicationmentioning
confidence: 99%
“…Se ha utilizado ampliamente para medir la habilidad empática de los terapeutas y para el estudio de la empatía en las relaciones enfermeras-pacientes (Kunst-Wilson et al, 1981). Kagan et al, 1967) Objetivo del instrumento.…”
Section: Revista De Psicopatología Y Psicología Clínicaunclassified